ARTERIAL HYPERTENSION AND LEFT VENTRICULAR REMODELLING IN ELDERLY PATIENTS - I. A. Bakulina; E. G. Mutalova; L. N. Khusainova; Kh. M. Mustafin; R. I. Sadikova; L. N. Mingazetdinova; E. R. Smakaeva (Российский кардиологический журнал)
In total, 104 elderly patients with arterial hypertension (AH) and 20 healthy controls were examined. Thirty-four individuals had essential AH (EAH), and 70 – isolated systolic AH (ISAH). Statistically significant increase in blood pressure (BP) variability, reduction in night-time diastolic BP (DBP) combined with high systolic BP (SBP) level, and an increase in temporal index and night-time BP drop were maximal in ISAH patients. Disturbed systolic and diastolic left ventricular function was associated with transitory myocardial ischemia (79,7%) and silent night-time ischemia (SNI). SNI was characterised by higher SBP levels, and ISAH – by decreased night-time DBP. In elderly AH patients, cerebral perfusion was reduced, and in ISAH, adaptive and compensatory potential of cerebral vessels was also decreased.